2021
DOI: 10.12688/gatesopenres.13206.1
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of the rollout of pneumococcal conjugate vaccines in rural India using a digital tracking platform

Abstract: Background: In 2017, the pneumococcal conjugate vaccine (PCV) was introduced into the Indian immunization program as a priority. However, monitoring the implementation of this program has been a major challenge in rural India. Novel digital health platforms, used to track vaccine delivery, can address this issue. Methods: We analyzed data collected in a rural part of the Udaipur District of India, which recently introduced PCV13 into the routine immunization program. The data were collected by Khushi Baby, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…13 Responding to the above call, India introduced PCV in 2017 in a phased manner across 5 high-burden Indian states, Bihar, Himachal Pradesh, Madhya Pradesh, Rajasthan, and Uttar Pradesh. 10,14 However, the Government of India, decided in the 2021 to 2022 budget to rapidly expand the PCV under the UIP throughout the country. 15 The process of a new vaccine introduction has never been an easy task to accomplish.…”
Section: Introductionmentioning
confidence: 99%
“…13 Responding to the above call, India introduced PCV in 2017 in a phased manner across 5 high-burden Indian states, Bihar, Himachal Pradesh, Madhya Pradesh, Rajasthan, and Uttar Pradesh. 10,14 However, the Government of India, decided in the 2021 to 2022 budget to rapidly expand the PCV under the UIP throughout the country. 15 The process of a new vaccine introduction has never been an easy task to accomplish.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the result of years of clinical research and the prevailing disease burden of pneumococcal disease in the country, a decision to roll out PCV in the entire country was made. However, before the vaccine could be rolled out, the COVID-19 pandemic hit the world [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic sensitivity patternsSulfamethoxazole-trimethoprim and teicoplanin sensitivity were observed in one tested isolate each. Sensitivity data was unavailable for some isolates for respective antibiotics the third dose at <12 months of age[39]. It is to be observed that this study population represents one of the states implementing the vaccination program, and the study population represents a minuscule amount of the country's population.…”
mentioning
confidence: 99%